Subtypes of Acute Ischemic Stroke - Fouzia Aurangzeb, Lubna Meraj , Muhammad Arif , Muhammad Qasim Rasool , Masood Ahmad (Journal of Rawalpindi Medical College, 2016)
Background: To determine the frequency of various subtypes of acute ischemic stroke among patients using the TOAST criteria. Methods: In this prospective, cross sectional study 156 consecutive stroke patients fulfilling the inclusion criteria were recruited. Information on risk factors like age, gender, diabetes and hypertension was collected. Physical and neurological examination was done and relevant investigations were reviewed, to classify the subtype of stroke according to TOAST criteria. . Risk factors like age, gender, diabetes and hypertension were compared with stroke subtypes after stratification using the chi-square test with significance at p < 0.05. Results: Out of the 156 patients with acute ischemic stroke, mean age at presentation was 63.51 years. Among them 75% had hypertension and 48.1% were diabetics. The various subtypes of acute ischemic stroke were Large artery atherosclerosis(35.3%)which was the commonest cause. Large artery atherosclerosis was found to be more common in females (47.1% vs 25.6%) whereas cardioembolic strokes were more common in males (29.1% vs 17.1%) (p value 0.02). When hypertension and diabetes was compared with stroke subtypes the results were statistically insignificant (p value. >0.05). Conclusion: Higher incidence of large artery and cardioembolic disease was found. Preventive efforts against the burden of ischemic stroke should focus on risk factor intervention for each patient according to subtype rather than ischemic stroke as a whole.